An ethnomathematical exploration of lipa’ sabbe weaving in Sengkang - Djam’an, Nurwati; Ashari, Elza Rahayu (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to systematically explore and analyze geometric transformation concepts embedded in Lipa’ Sabbe weaving from an ethnomathematical perspective and to examine their relevance for culturally responsive mathematics education. Method:  A qualitative ethnographic approach was employed, involving participant observation, in depth interviews, and documentation with purposively selected informants, including a cultural policymaker, a silk entrepreneur, and an experienced traditional weaver in Sengkang, South Sulawesi. The collected data were analyzed using inductive thematic analysis and constant comparison techniques to identify patterns related to mathematical activities and geometric transformations. Findings: The findings reveal that Lipa’ Sabbe weaving embodies key geometric transformation concepts, including translation, reflection, rotation, and dilation, which are reflected in the structured arrangement of motifs. In addition, the weaving process involves fundamental mathematical activities such as counting, measuring, designing, locating, playing, and explaining. Significance: These results demonstrate that Lipa’ Sabbe weaving represents a culturally situated mathematical practice, providing a meaningful context for linking abstract geometric concepts with real world cultural experiences. The study contributes to ethnomathematics by offering a systematic analytical framework and highlights its potential for developing culturally grounded mathematics learning.